The most patient man - Khan, Saniyasnain; Anand, Achla Anand, Achla, K. (Goodword Kidz New Delhi, 2003)
The Most Patient Man is a poignant narrative that delves into the virtues of patience and perseverance, showcasing how enduring life's challenges can lead to profound personal growth and understanding.